2021
DOI: 10.3389/fphar.2021.680209
|View full text |Cite
|
Sign up to set email alerts
|

The Regenerative Potential of bFGF in Dental Pulp Repair and Regeneration

Abstract: Regenerative endodontic therapy intends to induce the host’s natural wound-healing process, which can restore the vitality, immunity, and sensitivity of the inflammatory or necrotic pulp tissue destroyed by infection or trauma. Myriads of growth factors are critical in the processes of pulp repair and regeneration. Among the key regulatory factors are the fibroblast growth factors, which have turned out to be the master regulators of both organogenesis and tissue homeostasis. Fibroblast growth factors, a famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 127 publications
(171 reference statements)
0
9
0
Order By: Relevance
“…bFGF stimulated the proliferation of SCAP under serum-free conditions [18] . bFGF also stimulates cell stemness, DNA synthesis, and the proliferation of dental pulp cells, but inhibits apoptosis [10] , [31] , [34] , [35] , indicating the general growth-stimulating effect of bFGF.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…bFGF stimulated the proliferation of SCAP under serum-free conditions [18] . bFGF also stimulates cell stemness, DNA synthesis, and the proliferation of dental pulp cells, but inhibits apoptosis [10] , [31] , [34] , [35] , indicating the general growth-stimulating effect of bFGF.…”
Section: Discussionmentioning
confidence: 98%
“…These events are differentially regulated through receptor activation and signaling [32] . Four FGF receptors (FGFR1, 2, 3, and 4), are differentially expressed in different kinds of tissues and organs [10] , but upstream stimulators and downstream signaling molecules (e.g., phospholipase C gamma, leukemia inhibitory factor-signal transducers, activators of transcription [STAT], mitogen-activated protein kinase [MAPK], and phosphatidylinositol-4,5-bisphosphate 3-kinase [PI3K]-AKT) mediating different FGFR activation show some differences and remain to be clarified [10] , [32] , particularly in SCAP. We recently demonstrated FGFR1 and FGFR2 mRNA expression in SCAP and human dental pulp cells [18] , [31] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BFGF binds to tyrosine kinase FGF receptors 1–4 on the cell membrane, and phosphorylation occurs. Then, a cascade of intracellular signaling pathways, such as the RAS-MAPK, PI3K-AKT, PLCγ, and JAK/STAT, initiate cell migration, proliferation, and differentiation [ 49 ]. Five included studies used bFGF alone or in combination with other signaling molecules for pulp regeneration [ 22 , 31 , 32 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, FGF‐2 was found to be enhanced by dexamethasone by over 16‐fold compared to the control. Indeed, FGF‐2, a growth factor governing organogenesis and tissue homeostasis, plays an essential role in stemness maintenance and regulates dental pulp cells in a stage‐specific manner 64,65 . Another study further explored its role in odontoblast differentiation in αSMACre‐tdTomato mice model and concluded that early and pulsed exposure to FGF‐2 facilitated the differentiation of odontoblasts and promoted the formation of reparative dentin devoid of osteoblasts 66 .…”
Section: Discussionmentioning
confidence: 99%